Sosialisasi Program Kerja Pengembangan Sumber Daya Manusia Perempuan di Kelurahan Cepoko Kecamatan Gunungpati Kota Semarang - Sintya Oktarina; Firda Nisafera Ulfa; Dheny Indra Gunawan; Eka Mustikasari; Sauca Ananda Pranidana (ARDHI : Jurnal Pengabdian Dalam Negri, 2024)
According to the Central Statistics Agency (BPS), the level of education and welfare in the family greatly influences the quality of human resources in Indonesia. Therefore, efforts to strengthen family functions, such as increasing parental education and social welfare programs, are key in accelerating national development. This increase in human resources includes knowledge and skills in processing agricultural products, especially rambutan fruit, crystal guava and longan into processed food products with higher selling value such as chips. Apart from that, this program also trains them in creative product packaging, marketing, bookkeeping, simple financial management, and the use of digital technology, including online learning applications and social media. With these skills, they are expected to be able to contribute to improving the family's economy, as well as opening up new business opportunities that support financial independence.